Application of acoustic emission (AE) technique in various materials (metal, woods and bricks) - Musa, J. (University Malaysia Sarawak, UNIMAS., 2002)
Acoustic Emission (AE) technique is a new term to many of us. Why acoustic emission technique is important in civil engineering work? It is important because we can detected and know the problems of the material.